Preliminary establishment of genetic transformation system for embryogenic callus of Acer truncatum ‘Lihong’ - Yang, Yipeng; Chan, Yuan; Wang, Yongge; Guo, Hao; Song, Lina; Zhang, Huali; Sun, Liping; Cong, Richen; Zhang, Hua (Frontiers in Plant Science, 2024)
Introduction Acer truncatum Bunge, belonging to the Acer genus in the Aceraceae family, is a commonly planted afforestation species across China, Japan, Korea, Europe, and North America. Renowned for its vibrant fall colors, it holds significant ecological and ornamental value. Methods In this study, Acer truncatum ' Lihong ' was used as the research object. Starting from the callus induction of explants, the embryogenic callus of Acer truncatum 'Lihong' was obtained by systematically optimizing the medium and culture conditions. Then, the candidate gene AtrGST894 screened by transcriptome sequencing was transformed into embryogenic callus by Agrobacterium-mediated transformation. The genetic transformation system of Acer truncatum 'Lihong' embryogenic callus was initially established by continuously adjusting the conditions of Agrobacterium tumefaciens infection receptor materials, thus laying a material foundation for the study of the molecular regulation mechanism of Acer truncatum 'Lihong' leaf color, and also preparing for the later molecular improvement breeding of Acer truncatum. Therefore, this study has important theoretical and practical significance. Results The results showed that the best medium for callus induction of Acer truncatum was 1/2MS+2 mg/L 2,4-D+0.3 mg/L 6-BA+0.5 mg/L NAA; The embryogenic callus induction medium of Acer truncatum was 1/2MS+3.0mg/L 6-BA+2.0mg/L TDZ+0.5mg/L IBA+0.1mg/L GA3; The proliferation medium of embryogenic callus of Acer truncatum was WPM+1.0mg/L TDZ+0.5mg/L IBA+0.1mg/L GA3+3mg/L 6-BA+1.0mg/L KT; The infection experiment of Agrobacterium tumefaciens on the embryogenic callus of Acer truncatum showed that the best antibacterial medium was WPM+30g/L sucrose+8g/L agar+0.5g/L acid-hydrolyzed casein+0.2mg/L KT+1.0 mg/L TDZ+0.5 mg/L IBA+0.1 mg/L GA3+200mmol/L carboxybenzyl+200mg/L cephalosporin, and then WPM+30g/L sucrose+8g/L agar+0.5g/L acid-hydrolyzed casein+0.2mg/L KT+1.0 mg/L TDZ+0.5 mg/L IBA+0.1 mg/L GA3+300mmol/L carboxybenzyl+200mg/L cephalosporin+25mg/L hygromycin. Screening medium screening, The obtained embryogenic callus browning rate, pollution rate and mortality rate were the lowest, and maintained vigorous growth. Discussion The embryogenic callus was used as the infection material to verify that we successfully transferred the target gene into the embryogenic callus, which means that the genetic transformation system of Acer truncatum embryogenic callus was partially completed, and the infection process could be effectively inhibited. Although there was partial browning, it could continue to proliferate. Therefore, in future experiments, the focus is still to continue to verify the optimal conditions for optimizing the genetic transformation of Acer truncatum embryogenic callus and to solve the problems of difficulty in embryonic callus germination.